Electrospun cellulose nanofibers membranes with photothermal/pH-induced switchable wettability for oil-water separation and elimination of bacteria - Fang, Xubo; Du, Yuhan; Nawaz, Haq; Li, Xin; Yan, Ning; Zheng, Wenqiu; Li, Deqiang; Xu, Feng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Considering the substantial annual global discharge of oily wastewater, there exists a crucial requirement to develop smart membranes that possess environmentally sustainable attributes, tunable wettability, and potent antibacterial properties, enabling efficient and controlled separation of oil/water mixtures. Here, a photothermal/pH-responsive electrospun cellulose nanofibers (ECF-P-Fe3O4-N) membrane endowed with wettability modulation and bacterial elimination capabilities was successfully prepared. The advancement in the fabrication method stemmed from the ingenious integration of three key strategies: the interpenetrating network formation between cellulose and the thermosensitive polymer, the co-precipitation embedding of photothermal medium (Fe3O4 NPs), and the chemical grafting of aminosilane. The resultant ECF-P-Fe3O4-N membrane exhibited fast and reversible wettability transitions between high hydrophilicity (under acid or high-temperature stimulation) and hydrophobicity (under alkali or low-temperature stimulation), achieving on-demand separation of diverse immiscible oil-water mixtures and surfactant-stabilized emulsions. The maximum separation flux for oil-water emulsions attained a value of 225.6 L m−2 h−1, accompanied by a separation efficiency surpassing 98.53 %. It also possessed strong elimination of bacteria, satisfying for the long-lasting contact usage. This work holds significant implications in designing smart membranes for remotely controlling the oil-water separation. The photothermal/pH-responsive electrospun cellulose nanofibers membranes, capable of wettability regulation and bacterial elimination, were successfully fabricated through the integration of three strategies: the formation of interpenetrating networks, the co-precipitation embedding of Fe3O4 NPs, and the chemical grafting of aminosilane. The resultant ECF-P-Fe3O4-N membrane exhibited rapid and reversible wettability transitions, thereby enabling high-efficiency separation of oil-water mixtures and emulsions. [Display omitted] •A smart electrospun cellulose nanofibers membrane was successfully prepared.•Reversible transitions of hydro-phil/phobia facilitate on-demand oil-water separation.•The membrane achieves a maximum flux of 225.6 L m−2 h−1 with >98.53 % efficiency.•It is highly antibacterial and suitable for prolonged contact use.